2006
DOI: 10.1080/23808985.2006.11679054
|View full text |Cite
|
Sign up to set email alerts
|

The Advantages of Compliance or the Disadvantages of Noncompliance? A Meta-Analytic Review of the Relative Persuasive Effectiveness of Gain-Framed and Loss-Framed Messages

Abstract: A meta-analytic review of the relative persuasiveness of gain-and loss-framed messages (based on 165 effect sizes, N = 50,780) finds that loss-framed appeals are not generally more persuasive than gain-framed appeals. For encouraging disease prevention behaviors, gain-framed appeals are more persuasive than loss-framed appeals; for encouraging disease detection behaviors, gainand loss-framed appeals do not differ significantly in persuasiveness. The relative persuasiveness of differently framed appeals seems l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
178
3
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(197 citation statements)
references
References 66 publications
(75 reference statements)
14
178
3
2
Order By: Relevance
“…Neutral events such as unfamiliar symbols become capable of evoking and reinforcing behavior only when behavior is differentially reinforced in their presence (e.g., 15). In accord with these findings, communications researchers have consistently found that signs, informative brochures, and other messages which highlight the advantages of adopting the practices that they recommend are more effective than equally informative messages that stress the disadvantages of noncompliance with recommendations (16). While warnings provide necessary deterrents to inappropriate practices, these findings indicate that identifying symbols are likely to encourage the use of recycled water only when they represent its capabilities in addition to its limitations.…”
Section: Introductionmentioning
confidence: 88%
“…Neutral events such as unfamiliar symbols become capable of evoking and reinforcing behavior only when behavior is differentially reinforced in their presence (e.g., 15). In accord with these findings, communications researchers have consistently found that signs, informative brochures, and other messages which highlight the advantages of adopting the practices that they recommend are more effective than equally informative messages that stress the disadvantages of noncompliance with recommendations (16). While warnings provide necessary deterrents to inappropriate practices, these findings indicate that identifying symbols are likely to encourage the use of recycled water only when they represent its capabilities in addition to its limitations.…”
Section: Introductionmentioning
confidence: 88%
“…Frames can also offer a particular way to understand an issue and can create and shape individuals' thoughts and opinions on particular issues (Entman, 1993;Kinder, 1998). Framing has been shown to influence a myriad of health decisions, such as HIV testing, cancer screening, flu shots, sunscreen use, and safe driving (Apanovitch, McCarthy, & Salovey, 2003;Detweiler, Bedell, Salovey, Pronin, & Rothman, 1999;Finney & Iannoti, 2002;McCall, Johnson, & Rothman, 2002;Meyerowitz & Chaiken, 1987;Millar & Millar, 2000;O'Keefe & Jensen, 2006). In our study, framing the cause of nicotine addiction as either genetically or environmentally influenced could affect smokers' intentions to try a nicotine vaccine if one becomes available.…”
Section: Communication Effects: Framingmentioning
confidence: 78%
“…Fourth, the different result between public policy support and individual intentions may have emerged because thoughts about public policy, unlike individual behavior intention (which has a more complex array of contributing factors), are more susceptible to the influence of the PSA. & Jensen, 2006), it is not surprising that individual behavior intention was not susceptible to framing effects. Individual behavior or behavior intention are extremely complex and are determined by multiple individual, situational, and social factors.…”
Section: Discussionmentioning
confidence: 99%